The concept of economic efficiency in agriculture - Rodica Chetroiu; Ion Călin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The economic efficiency is a concept with a complex content, which expresses the useful effect achieved in an economic activity, in relation to the requested expenditures, or the effort for its realization. Through its applicative side, the efficiency (e) can be defined as a quantitative ratio between the effects (E) and the resources or efforts (R) made to obtain them, or, in other words, achieving maximum effect with a specified level of consumptions, or reaching the determined effect with minimum consumption: e = E / R max (maximizing the effects obtained per unit of allocated, consumed resources); e = R / E min (minimizing the resource consumption per unit of effect achieved). This concept is the most important qualitative indicator of the economic development, a key factor in accelerating economic growth. Applied in agriculture, it represents the obtaining the maximum amount of production per hectare or per animal, with minimal expenditure of manpower and materials. Determination of economic efficiency must be based on knowledge of the elements that characterize the production effort and having three main sources: the optimal use of resources, rational use of labour and production management.
Keywords: 330; economic efficiency; effects; resources; agriculture; concept